Ultraviolet aging resistant photovoltaic cable and preparation method thereof
By mixing and granulating raw materials of polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium-aluminum hydrotalcite, titanium dioxide and additives, and covering it on the surface of the cable core through melt extrusion technology to form a sheath layer that resists UV aging, the problem of photovoltaic cable sheath layer aging due to poor UV resistance is solved, and the cable's UV resistance and service life is significantly improved.
Patent Information
- Application Number
- CN202510274135.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
After long-term outdoor use, the sheath layer of the photovoltaic cable ages due to poor UV resistance, resulting in damage to safety.
The raw materials including polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium-aluminum hydrotalcite, titanium dioxide and additives are mixed and granulated, and the surface of the cable core is coated through melt extrusion technology to form a sheath layer that is resistant to UV aging. The modified magnesium-aluminum hydrotalcite is intercalated and the intercalator includes ammonium salt and hydroxybenzophenone.
It significantly improves the UV resistance of the photovoltaic cable sheath layer, extends the service life of the cable, and ensures its safety. It is especially suitable for photovoltaic equipment installation in plateau areas.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable processing, and in particular to an anti-ultraviolet aging photovoltaic cable and a preparation method thereof. Background Art
[0002] Photovoltaic cables are special cables in solar power generation systems, mainly used for power transmission between components and between components and inverters. The basic structure of photovoltaic cables includes: conductor core, insulation layer and sheath layer. The conductor is usually made of high-purity oxygen-free copper or tinned copper, the insulation layer is usually made of polymer, and the sheath layer is made of polymer or composite material.
[0003] Since photovoltaic cables are often used outdoors in strong light environments, the sheath layer of such cables is prone to aging after long-term use due to lack of UV resistance, resulting in the safety of photovoltaic cables not being effectively guaranteed. How to improve the UV resistance of photovoltaic cable sheath layer materials is a technical problem that technicians in this field need to solve. Summary of the invention
[0004] One of the problems solved by the present invention is how to provide a photovoltaic cable with excellent anti-ultraviolet performance.
[0005] In order to solve at least one of the above problems, the present invention provides a method for preparing a UV-resistant photovoltaic cable, comprising: S1, mixing and granulating raw materials including polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium aluminum hydrotalcite, titanium dioxide and additives to obtain a masterbatch; S2, melt-extrude the masterbatch, and coat it on the surface of the cable core as a sheath layer to obtain a photovoltaic cable; The modified magnesium aluminum hydrotalcite is subjected to intercalation treatment, and the intercalation agents used in the intercalation treatment include ammonium salt and hydroxybenzophenone.
[0006] In any of the above technical solutions, based on the total addition amount of titanium dioxide as 100wt%, the titanium dioxide includes: titanium dioxide powder A, 20wt% to 25wt%; titanium dioxide powder B, 45wt% to 50wt%; titanium dioxide powder C, 30wt% to 35wt%; wherein the average particle size D50 of titanium dioxide powder A is A Smaller than the average particle size D50 of titanium dioxide powder B B , the average particle size D50 of titanium dioxide powder B B Smaller than the average particle size D50 of titanium dioxide powder C C .
[0007] In any of the above technical solutions, the particle size range of the titanium dioxide powder A is greater than 50nm and less than 100nm, the particle size range of the titanium dioxide powder B is greater than 100nm and less than 200nm, and the particle size range of the titanium dioxide powder C is greater than 200nm and less than 350nm.
[0008] In any of the above technical solutions, in S1, the mass ratio of polyvinyl chloride: polyethylene: ethylene-vinyl acetate copolymer: modified magnesium aluminum hydrotalcite: titanium dioxide: additive = 100: (30-35): (20-25): (6-12): (4-6): (2-6).
[0009] In any of the above technical solutions, in S1, based on the total amount of additives added as 100wt%, the additives include: 35wt% to 40wt% of a plasticizer, diisodecyl phthalate, 25wt% to 30wt% of a stabilizer, calcium zinc dimerate, 10wt% to 20wt% of an antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 15wt% to 25wt% of a lubricant, glyceryl monostearate.
[0010] In any of the above technical solutions, in S1, the polyethylene is a linear low-density polyethylene.
[0011] In any of the above technical solutions, the cable core includes, from inside to outside, a conductor, a conductor shielding layer, an insulating layer, and an insulating shielding layer.
[0012] In any of the above technical solutions, in S1, the mixing temperature of the mixing and granulation is 80°C to 100°C, the mixing speed is 400r / min to 800r / min, and the mixing time is 20min to 30min.
[0013] In any of the above technical solutions, in S2, the melting temperature of the melt extrusion is 160° C. to 220° C., and the melting time is 20 min to 40 min.
[0014] In any of the above technical solutions, the polyvinyl chloride is subjected to carboxyl modification, the intercalant further comprises serine, and the polyvinyl chloride and the modified magnesium aluminum hydrotalcite are organically linked through an esterification reaction.
[0015] In any of the above technical solutions, the carboxylation modification treatment comprises: using a compound having at least one carboxyl group and at least one thiol group to react with polyvinyl chloride particles by heating and refluxing in a solvent system.
[0016] In any of the above technical solutions, the esterification reaction is carried out under heating conditions using an inorganic acid as a catalyst.
[0017] In any of the above technical solutions, S1 specifically includes: S11, mixing polyvinyl chloride and modified magnesium aluminum hydrotalcite, using an acid as a catalyst, heating and refluxing in a solvent system to obtain a first mixture; S12, mixing and granulating the first mixture with polyethylene, ethylene-vinyl acetate copolymer, titanium dioxide and additives to obtain master batches.
[0018] In any of the above technical solutions, the modified magnesium aluminum hydrotalcite is prepared by the following steps: A1, dissolving ammonium salt and serine in water to obtain an aqueous phase; A2, dissolving hydroxybenzophenone in N-methylpyrrolidone to obtain an organic phase; A3, firstly, uniformly dispersing magnesium aluminum hydrotalcite, aqueous phase and sodium dodecyl sulfate by ultrasonication, then adding organic phase and cyclohexane, mixing and ultrasonically emulsifying to obtain an emulsion; A4. The emulsion is fed into a reactor and subjected to hydrothermal treatment under heating and pressurization conditions to obtain modified magnesium aluminum hydrotalcite.
[0019] The present invention also provides an anti-ultraviolet aging photovoltaic cable, which is obtained by adopting the preparation method of any of the above technical solutions.
[0020] Beneficial Effects The present invention provides a method for preparing an anti-ultraviolet aging photovoltaic cable, wherein the method firstly adopts raw materials including polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium aluminum hydrotalcite, titanium dioxide and an auxiliary agent to mix and granulate to obtain a master batch. Then, the master batch is melt-extruded and coated on the surface of a cable core as a sheath layer to obtain a photovoltaic cable. The modified magnesium aluminum hydrotalcite is subjected to an intercalation treatment, and the intercalation agent used in the intercalation treatment includes ammonium salt and hydroxybenzophenone.
[0021] In the first aspect, the present invention controls the basic components and proportions of the sheath layer material used in the photovoltaic cable. The three main polymer raw materials used in the sheath layer material are polyvinyl chloride, polyethylene and ethylene-vinyl acetate copolymer. Among many polymer materials, polyvinyl chloride has relatively good thermal stability, chemical stability and mechanical strength. Polyethylene and polyvinyl chloride have a certain compatibility during processing. Adding an appropriate amount of polyethylene can improve the processing performance of polyvinyl chloride and improve its fluidity and extrusion efficiency. Adding ethylene-vinyl acetate copolymer to polyvinyl chloride material can improve the flexibility of polyvinyl chloride material, thereby improving its tensile properties.
[0022] In the second aspect, the present invention improves the inorganic auxiliary agent component of the sheath material used in photovoltaic cables. For the cable sheath layer with polymer as the main raw material, it is easy to decompose, age, lose elasticity and reduce mechanical properties under long-term illumination of natural light. The reason for the above phenomenon is mainly that the ultraviolet rays with higher photon energy in natural light will destroy the chemical bonds in the plastic molecules, resulting in chain breakage, and will also cause the plastic polymer material to form chromophores, resulting in discoloration. Therefore, polymer materials will become brittle under long-term high-intensity natural light, and their strength, elasticity and durability will be reduced. In order to avoid or alleviate the above phenomenon, anti-ultraviolet components are usually added to the sheath material. Among them, titanium dioxide is a relatively widely used anti-ultraviolet component. The mechanism for achieving anti-ultraviolet effect is mainly because titanium dioxide has a higher refractive index, which enables it to effectively reflect and scatter ultraviolet rays. When ultraviolet rays are irradiated to the surface of the material containing titanium dioxide, a considerable part of the ultraviolet rays will be reflected back or scattered in other directions, thereby reducing the direct irradiation of ultraviolet rays to the material. Considering that the effect of titanium dioxide on ultraviolet light is limited to reflection and scattering, the present invention further introduces hydroxybenzophenone into the sheath layer with polyvinyl chloride as the main material. Hydroxybenzophenone, as an ultraviolet absorber, contains a conjugated system in its molecular structure, and such a structure enables it to effectively absorb ultraviolet rays. The present invention improves the anti-ultraviolet performance of the sheath layer by simultaneously introducing titanium dioxide and hydroxybenzophenone into the sheath layer. Due to the high altitude of the plateau area, the thin atmosphere, and the high intensity of solar radiation, photovoltaic equipment can obtain more solar energy and have higher power generation efficiency. Therefore, there is a large demand for laying photovoltaic cables in the plateau area. The blocking effect of the ozone layer on ultraviolet rays in the plateau area is weakened, so the ultraviolet penetration ability in the plateau area is significantly enhanced. The processing method of introducing ultraviolet reflective substances and ultraviolet absorbing substances into high molecular polymer materials of the present invention is more conducive to obtaining photovoltaic cables suitable for the installation of photovoltaic equipment in plateau areas.
[0023] In the third aspect, the present invention introduces hydroxybenzophenone into the interlayer of magnesium aluminum hydrotalcite by intercalation treatment. Considering that hydroxybenzophenone is an organic ultraviolet absorber, it has the problem of easy migration and poor thermal stability. Since the interlayer region of magnesium aluminum hydrotalcite contains a large amount of water molecules that desorb and absorb heat at high temperature, inserting hydroxybenzophenone into the interlayer of magnesium aluminum hydrotalcite not only helps to fix hydroxybenzophenone and limit its migration, but also can protect it from high temperature to avoid its failure under natural conditions of long-term high temperature. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below in conjunction with specific embodiments of the present invention.
[0025] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0026] The present invention provides a method for preparing a photovoltaic cable resistant to ultraviolet aging, wherein the photovoltaic cable comprises at least a cable core and a sheath layer. The core structure of the cable core is a conductor, and an insulating layer is wrapped around the outer periphery of the conductor. A conductor shielding layer can be arranged between the conductor and the insulating layer. An insulating shielding layer can also be wrapped around the outer periphery of the insulating layer. In addition, a water-blocking tape layer can also be arranged outside the insulating shielding layer. The conductor is generally twisted with high-purity oxygen-free copper or tinned copper, and the insulating layer is generally prepared with polymer compounds such as polyvinyl chloride, polyethylene, ethylene-propylene rubber, or a combination thereof. The conductor shielding layer and the insulating shielding layer are used to smooth the electric field distribution, prevent local discharge and electromagnetic interference, and generally can be made of metal materials or semiconductor materials. The water-blocking tape layer is usually made of highly absorbent fibers or non-woven fabrics impregnated with highly absorbent resins.
[0027] The sheath layer is usually made of high molecular polymer or composite material. Its function is to protect the cable core and prevent the cable core from being damaged by stretching, bending or extrusion during installation or use. In addition, the sheath layer usually needs to have functions such as waterproof and moisture-proof, corrosion-resistant, heat-resistant, fire-retardant, and UV-resistant.
[0028] The present invention uses polyvinyl chloride, polyethylene, and ethylene-vinyl acetate copolymer as main raw materials to prepare the sheath layer of the photovoltaic cable. The overall preparation process of the present invention is to weigh the above raw materials and necessary inorganic or organic additives and mix them to make master batches, then melt the master batches and extrude them through a screw device, and coat them on the surface of the cable core to form the sheath layer.
[0029] Specifically, the preparation method of the present invention comprises: S1, mixing and granulating raw materials including polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium aluminum hydrotalcite, titanium dioxide and additives to obtain a masterbatch; S2. Melt and extrude the masterbatch, and coat it on the surface of the cable core as a sheath layer to obtain a photovoltaic cable.
[0030] The present invention preferably uses polyvinyl chloride with an average molecular weight of 50,000-100,000. The polyethylene used in the present invention is preferably linear low-density polyethylene. The additives used in the present invention include plasticizers, stabilizers, antioxidants and lubricants. Among them, the functions of the above additives belong to the prior art, and the present invention will not be repeated here.
[0031] Preferably, in S1, based on the total amount of additives added as 100wt%, the additives include: 35wt% to 40wt% of a plasticizer, diisodecyl phthalate, 25wt% to 30wt% of a stabilizer, calcium zinc dimerate, 10wt% to 20wt% of an antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 15wt% to 25wt% of a lubricant, glyceryl monostearate.
[0032] Further preferably, in S1, based on the total amount of additives added as 100wt%, the additives include: 40wt% of a plasticizer, diisodecyl phthalate, 25wt% of a stabilizer, calcium zinc dimerate, 20wt% of an antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 15wt% of a lubricant, glyceryl monostearate.
[0033] Regarding the component ratio, preferably, in S1, by mass ratio, polyvinyl chloride: polyethylene: ethylene-vinyl acetate copolymer: modified magnesium aluminum hydrotalcite: titanium dioxide: additive = 100: (30-35): (20-25): (6-12): (4-6): (2-6).
[0034] It can be understood that the main raw material of the sheath material of the present invention is polyvinyl chloride, and appropriate polyethylene can improve the processing performance of polyvinyl chloride, increase its fluidity and extrusion efficiency, and ethylene-vinyl acetate copolymer is used to improve the flexibility and tensile strength of the sheath layer.
[0035] In the present invention, the modified magnesium aluminum hydrotalcite is subjected to intercalation treatment, and the intercalation agent used in the intercalation treatment includes ammonium salt and hydroxybenzophenone. Preferably, the intercalation agent further includes serine. Magnesium aluminum hydrotalcite belongs to layered double hydroxides (LDH), which is a compound with a special layered structure. Magnesium aluminum hydrotalcite itself can be used as a flame retardant. The conjugated structure of hydroxybenzophenone can absorb ultraviolet rays and convert them into heat energy or other forms of energy. Considering the conjugated structure (benzene ring and carbonyl group) can absorb ultraviolet rays and convert them into heat energy or other forms of energy. Considering the problem of easy migration and poor thermal stability of hydroxybenzophenone, the present invention inserts hydroxybenzophenone into the interlayer of magnesium aluminum hydrotalcite. In order to ensure smooth intercalation, ammonium salt is used as an auxiliary intercalation agent to assist in opening the interlayer distance of magnesium aluminum hydrotalcite. Serine can cooperate with ammonium salt to assist in intercalation by releasing ammonium ions. By inserting hydroxybenzophenone into the interlayer of magnesium aluminum hydrotalcite, it not only helps to fix the hydroxybenzophenone and limit its migration, but also can protect it from high temperature and avoid its failure under natural conditions of long-term high temperature.
[0036] In addition to using the ultraviolet absorber in combination with titanium dioxide, the present invention also screens and controls the particle size of titanium dioxide. This is because the reflection and scattering effect of titanium dioxide on ultraviolet light is related to its particle size. In general, titanium dioxide with a particle size less than 400nm has a relatively good reflection and scattering effect on ultraviolet light, and titanium dioxide with a particle size greater than 400nm has enhanced hiding power, but weakened anti-ultraviolet performance. In addition, titanium dioxide of different particle sizes also has differences in the reflection and scattering effect on ultraviolet light. Titanium dioxide greater than 100nm is mainly Mie scattering, which has a certain effect on the reflection and scattering of ultraviolet light, but excessive addition will cause whitening. Titanium dioxide less than 100nm is mainly Rayleigh scattering, and its scattering effect on ultraviolet light is very significant, but excessive addition will lead to poor dispersibility, and titanium dioxide with a small particle size is more active, and it is easy to produce too many free radicals, which are captured by hydrogen chloride slowly decomposed and released by polyvinyl chloride during long-term use, resulting in aging of polyvinyl chloride materials.
[0037] Therefore, the titanium dioxide used in the present invention includes three powders with different particle sizes. Taking the total amount of titanium dioxide added as 100wt%, the titanium dioxide added in the present invention includes: titanium dioxide powder A, 20wt% to 25wt%; titanium dioxide powder B, 45wt% to 50wt%; titanium dioxide powder C, 30wt% to 35wt%; wherein the average particle size D50 of titanium dioxide powder A is A Smaller than the average particle size D50 of the titanium dioxide powder B B , the average particle size D50 of titanium dioxide powder B B Smaller than the average particle size D50 of titanium dioxide powder C C .
[0038] Specifically, the particle size range of titanium dioxide powder A is greater than 50 nm and less than 100 nm, the particle size range of titanium dioxide powder B is greater than 100 nm and less than 200 nm, and the particle size range of titanium dioxide powder C is greater than 200 nm and less than 350 nm.
[0039] Preferably, the particle size range of titanium dioxide powder A is greater than 50 nm and less than 80 nm, the particle size range of titanium dioxide powder B is greater than 120 nm and less than 150 nm, and the particle size range of titanium dioxide powder C is greater than 200 nm and less than 250 nm.
[0040] It is understood that the titanium dioxide powders of different particle sizes used in the present invention can be directly purchased, or can be obtained by air flow screening or wet screening.
[0041] Preferably, in the present invention, polyvinyl chloride is treated with carboxylation modification, and polyvinyl chloride and modified magnesium aluminum hydrotalcite are organically linked through esterification reaction. The purpose of the above treatment method is: on the one hand, the organic link between polyvinyl chloride and modified magnesium aluminum hydrotalcite can be used to avoid or prevent the agglomeration of magnesium aluminum hydrotalcite in the polymer material; on the other hand, magnesium aluminum hydrotalcite can be used to prevent or reduce the contact between polyvinyl chloride and titanium dioxide, and the ultraviolet absorber between the magnesium aluminum hydrotalcite layers can absorb the remaining small amount of ultraviolet rays that cannot be scattered or reflected by titanium dioxide, which helps to limit or prevent the contact between ultraviolet rays and polyvinyl chloride materials.
[0042] Specifically, titanium dioxide (especially nano-scale titanium dioxide) not only reflects and scatters ultraviolet light, but also absorbs ultraviolet light to a certain extent. By absorbing ultraviolet light, the valence band electrons of titanium dioxide jump to the conduction band to form electron-hole pairs. Holes react with water molecules or hydroxyls adsorbed on the surface of the material to generate hydroxyl radicals. Electrons react with oxygen adsorbed on the surface of the material to generate superoxide radicals, and further reactions will also generate hydroxyl radicals. For high-molecular materials such as polyvinyl chloride, they slowly decompose and release hydrogen chloride during long-term use. Hydrogen chloride can capture the active free radicals generated by titanium dioxide, leading to and accelerating the degradation of polyvinyl chloride. By organically linking magnesium-aluminum hydrotalcite on the surface of polyvinyl chloride, not only can the contact between polyvinyl chloride and titanium dioxide be prevented or reduced, but the hydroxybenzophenone between the magnesium-aluminum hydrotalcite layers can also be used to absorb ultraviolet rays that are not reflected or scattered by titanium dioxide, further protecting polyvinyl chloride and preventing chemical bond breakage and decomposition caused by ultraviolet light excitation.
[0043] The above organic connection is achieved through an esterification reaction, which is carried out under heating conditions with an inorganic acid as a catalyst. In order to achieve the esterification reaction, ensure the chemical connection effect, and avoid the agglomeration of hydrotalcite, it is necessary to carboxylate the polyvinyl chloride and promote as much serine and hydroxybenzophenone as possible to enter the interlayer of the magnesium aluminum hydrotalcite.
[0044] The carboxylation modification treatment of polyvinyl chloride includes: using a compound having at least one carboxyl group and at least one thiol group to heat and reflux with polyvinyl chloride particles in a solvent system. Exemplarily, polyvinyl chloride can be treated with glutathione to obtain carboxylated polyvinyl chloride.
[0045] Specifically, the method of treating polyvinyl chloride with glutathione is: dissolving glutathione in water, adding triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol, heating and refluxing reaction, and obtaining carboxylated polyvinyl chloride. After obtaining carboxylated polyvinyl chloride, the solvent can be removed under negative pressure, and the solvent and acid binding agent can be recycled. Preferably, in terms of mass ratio, triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = (2-4): (4-6): (6-8): (20-30): (10-15): 100. The temperature of the heating reflux reaction is preferably 80°C to 90°C, and the time is 8h to 12h.
[0046] Glutathione is formed by the condensation of three amino acids, glutamic acid, cysteine and glycine, through peptide bonds, and has two carboxyl groups and one thiol group. In the above steps, triethanolamine and polyvinyl alcohol are used as acid-binding agents, and ethanol is mainly used as the reaction medium. By heating and refluxing, the thiol group of glutathione and the chlorine atom of polyvinyl chloride undergo a nucleophilic substitution reaction, thereby introducing the carboxyl group of glutathione into the macromolecular chain of polyvinyl chloride to obtain carboxylated polyvinyl chloride.
[0047] Before explaining the intercalation process, the preparation process of the magnesium-aluminum hydrotalcite of the present invention is first described. The magnesium-aluminum hydrotalcite can be prepared by a chemical method in an alkaline environment using magnesium salt and aluminum salt as raw materials.
[0048] Specifically, the magnesium aluminum hydrotalcite in the present invention can be prepared by the following steps: magnesium chloride and aluminum nitrate are uniformly dispersed in water according to a mass ratio of magnesium chloride: aluminum nitrate: water = (10-15): (20-25): 100 to obtain a magnesium aluminum salt solution; 6wt% to 12wt% of an alkali metal hydroxide aqueous solution is added dropwise to the magnesium aluminum salt solution and stirred until the pH value reaches 10 to 12, and after standing and aging for 2h to 4h, the solid is filtered, washed, and dried to obtain magnesium aluminum hydrotalcite; wherein the alkali metal hydroxide aqueous solution is an aqueous solution of sodium hydroxide or potassium hydroxide.
[0049] In order to promote more hydroxybenzophenone to enter the interlayer of magnesium aluminum hydrotalcite, the present invention uses small molecule ammonium salt and serine having amino and carboxyl groups to open the interlayer distance of magnesium aluminum hydrotalcite. Specifically, the modified magnesium aluminum hydrotalcite of the present invention is prepared by the following steps: A1, dissolving ammonium salt and serine in water to obtain an aqueous phase; A2, dissolving hydroxybenzophenone in N-methylpyrrolidone to obtain an organic phase; A3, firstly, uniformly dispersing magnesium aluminum hydrotalcite, aqueous phase and sodium dodecyl sulfate by ultrasonication, then adding organic phase and cyclohexane, mixing and ultrasonically emulsifying to obtain an emulsion; A4. The emulsion is fed into a reactor and subjected to hydrothermal treatment under heating and pressurization conditions to obtain modified magnesium aluminum hydrotalcite.
[0050] Among them, the ammonium salt is specifically ammonium sulfate, and the hydroxybenzophenone is specifically 2,2',4,4'tetrahydroxybenzophenone. In A1, by mass ratio, ammonium salt: serine: water = (2-4): (10-20): 100. In A2, by mass ratio, hydroxybenzophenone: N-methylpyrrolidone = (6-12): 100. In A3, by mass ratio, magnesium aluminum hydrotalcite: aqueous phase: organic phase: sodium dodecyl sulfate: cyclohexane = (10-20): (40-60): (20-40): (2-4): (30-50). In A3, the frequency and power of ultrasonic dispersion can be selected and adjusted by a person skilled in the art, as long as uniform dispersion can be achieved. In addition to ultrasonic dispersion, magnetic stirring or manual stirring can also achieve the same purpose. The frequency of ultrasonic treatment is 60kHz to 80kHz, and the power is 400W to 600W. Sodium dodecyl sulfate is used as a surfactant and emulsifier. The purpose of ultrasonic treatment is to prepare the above raw materials used in A3 into an emulsion through ultrasonic waves, so as to improve the uniformity of the hydrothermal reaction and achieve uniform intercalation of the intercalant. The temperature of the hydrothermal treatment is 140°C to 160°C, and the pressure is 3MPa to 5Mpa. The time of the hydrothermal treatment is 2h to 3h. After the hydrothermal treatment, it is necessary to cool and release the pressure, filter the solids, use organic solvents and deionized water in turn, wash multiple times, and dry the solids to obtain modified magnesium aluminum hydrotalcite.
[0051] The interlayer spacing of magnesium aluminum hydrotalcite is about 0.77nm, and the van der Waals diameter of serine is above 0.56nm. The van der Waals diameter of serine is smaller than the interlayer spacing of magnesium aluminum hydrotalcite, and intercalation is theoretically feasible. However, in order to improve the intercalation effect, the present invention also adds small molecule ammonium sulfate as an intercalation agent. During the ultrasonic treatment process, ammonium sulfate chemically intercalates magnesium aluminum hydrotalcite, promotes its ammonium ions to enter the interlayer of magnesium aluminum hydrotalcite, and opens the interlayer spacing.
[0052] Serine contains amino and carboxyl groups. Ammonium sulfate produces hydrogen ions due to the hydrolysis of ammonium ions in water, thereby creating an acidic environment. Under acidic conditions, a proton in the carboxyl group of serine will be transferred to the amino group to form an ammonium ion. The further increased number of ammonium ions can exchange more cations between the hydrotalcite layers, help open the interlayer spacing of the hydrotalcite, and promote the intercalation of serine itself and 2,2',4,4'tetrahydroxybenzophenone into the magnesium-aluminum hydrotalcite. Therefore, the present invention needs to first mix and stir ammonium sulfate and serine with magnesium-aluminum hydrotalcite in an aqueous phase, then add 2,2',4,4'tetrahydroxybenzophenone, and perform ultrasonic emulsification to promote 2,2',4,4'tetrahydroxybenzophenone to enter the interlayer of the magnesium-aluminum hydrotalcite whose interlayer spacing has been pre-opened by ammonium sulfate and serine.
[0053] As mentioned above, in order to achieve the organic connection between magnesium aluminum hydrotalcite and polyvinyl chloride, it is necessary to drive the esterification reaction. Specifically, by heating and refluxing under acidic conditions, the carboxyl group of the modified polyvinyl chloride is chemically linked to the serine and the hydroxyl group of tetrahydroxybenzophenone inserted between the magnesium aluminum hydrotalcite layers through the esterification reaction, so that the intercalated modified magnesium aluminum hydrotalcite protects the polyvinyl chloride, limiting and reducing its contact with titanium dioxide and ultraviolet rays.
[0054] The esterification reaction needs to be carried out under the conditions of inorganic acid catalysis and heating. In the present invention, S1 specifically includes: S11, mixing polyvinyl chloride and modified magnesium aluminum hydrotalcite, using an acid as a catalyst, heating and refluxing in a solvent system to obtain a first mixture; S12, mixing and granulating the first mixture with polyethylene, ethylene-vinyl acetate copolymer, titanium dioxide and additives to obtain master batches.
[0055] The acid in S11 is phosphoric acid, and the solvent system is ethanol. In S11, by mass ratio, phosphoric acid: modified magnesium aluminum hydrotalcite: polyvinyl chloride: ethanol = (5-15): (6-12): 100: 300. The temperature of the heating reflux reaction is 80°C to 90°C, and the time of the heating reflux reaction is 2h to 4h. During the heating reflux reaction, a water-carrying agent can be used for timely dehydration. The water-carrying agent can be a molecular sieve or an organic water-carrying agent such as cyclohexane.
[0056] After the heating reflux reaction is completed, the solvent and catalyst are recovered, and the solids are extracted, washed, and dried to obtain a first mixture. The first mixture includes polyvinyl chloride organically linked to modified magnesium aluminum hydrotalcite, and also includes a small amount of polyvinyl chloride and modified magnesium aluminum hydrotalcite particles that have not participated in the reaction or have not completely participated in the reaction.
[0057] In S12, polyethylene: ethylene-vinyl acetate copolymer: titanium dioxide: additive = (30-35): (20-25): (4-6): (2-6). Among them, based on the mass of polyvinyl chloride used in S11, the amount of polyethylene used in S12 is controlled to be about one third of the mass of polyvinyl chloride in S11.
[0058] The mixing and granulation of raw materials such as polyvinyl chloride, polyethylene, and ethylene-vinyl acetate copolymer can be carried out using a mixer and a granulation device, and the size of the granules is preferably 0.5 mm to 2 mm. Melt extrusion is carried out using a melting device and a screw extrusion device, and the temperature range of the melting device and the speed of the screw extrusion device can be selected and adjusted by those skilled in the art. Preferably, in S1, the mixing temperature of the mixing and granulation is 80°C to 100°C, the mixing speed is 400r / min to 800r / min, and the mixing time is 20min to 30min.
[0059] The process of melt-extruding the masterbatch and coating it on the surface of the cable core is a relatively common prior art, and the present invention will not describe it in detail. Preferably, in S2, the melting temperature of the melt extrusion is 160° C. to 220° C., and the melting time is 20 min to 40 min.
[0060] Embodiment 1 In this embodiment, a magnesium aluminum hydrotalcite sample is prepared, and the preparation steps are as follows: 1. Disperse magnesium chloride and aluminum nitrate in distilled water at a mass ratio of magnesium chloride: aluminum nitrate: water = 10:20:100, stir evenly with magnetic force to obtain a magnesium aluminum salt solution; 2. Add 8 wt % sodium hydroxide aqueous solution to the magnesium aluminum salt solution and stir until the pH value reaches 11. After standing for 2 hours, filter the solid, wash once with ethanol, wash twice with water, and dry at 110° C. to obtain magnesium aluminum hydrotalcite sample 1.
[0061] Embodiment 2 This example prepares a carboxylated polyvinyl chloride sample, and the preparation steps are as follows: 1. Dissolve glutathione in water according to the mass ratio of triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = 2:6:6:20:10:100, then add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol and mix well to obtain a mixture; 2. The mixture was heated to reflux at 85°C for 10 hours, the solvent was removed, the reaction product was washed once with ethanol, twice with water, and dried with hot air at 80°C to obtain carboxylated polyvinyl chloride sample 1.
[0062] Embodiment 3 This example prepares a carboxylated polyvinyl chloride sample, and the preparation steps are as follows: 1. Dissolve glutathione in water according to the mass ratio of triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = 4:4:8:30:15:100, then add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol and mix well to obtain a mixture; 2. The same as step 2 of Example 2, obtain carboxylated polyvinyl chloride sample 2.
[0063] Embodiment 4 In this embodiment, a modified magnesium aluminum hydrotalcite sample is prepared, and the preparation steps are as follows: 1. Dissolve ammonium sulfate and serine in water at room temperature according to the mass ratio of ammonium sulfate: serine: water = 2:15:100 and stir evenly to obtain an aqueous phase; 2. Dissolve 2,2',4,4'-tetrahydroxybenzophenone in N-methylpyrrolidone at room temperature and stir evenly according to the mass ratio of 2,2',4,4'-tetrahydroxybenzophenone to N-methylpyrrolidone = 6:100 to obtain an organic phase; 3. The magnesium-aluminum hydrotalcite prepared in Example 1, the aqueous phase, and the sodium dodecyl sulfate were ultrasonically dispersed for 20 min in a mass ratio of magnesium-aluminum hydrotalcite: aqueous phase: organic phase: sodium dodecyl sulfate: cyclohexane = 15:50:30:3:40, and the organic phase and cyclohexane were added and mixed, and ultrasonically treated at a frequency of 60 kHz for 20 min using a 400 W ultrasonic device to obtain an emulsion. The emulsion was fed into a reactor and subjected to a hydrothermal treatment for 2.5 h at a temperature of 140° C. and a pressure of 3.5 MPa. After the hydrothermal treatment, the temperature was lowered and the pressure was released, and the solid was filtered, washed twice with acetone and water respectively, and dried to obtain a modified magnesium-aluminum hydrotalcite sample 1.
[0064] Embodiment 5 In this embodiment, a modified magnesium aluminum hydrotalcite sample is prepared, and the preparation steps are as follows: 1. Dissolve ammonium sulfate and serine in water at room temperature according to the mass ratio of ammonium sulfate: serine: water = 2:10:100 and stir evenly to obtain an aqueous phase; 2. Dissolve 2,2',4,4'-tetrahydroxybenzophenone in N-methylpyrrolidone at room temperature and stir evenly according to the mass ratio of 2,2',4,4'-tetrahydroxybenzophenone to N-methylpyrrolidone = 12:100 to obtain an organic phase; 3. The same as step 3 of Example 4, obtain a modified magnesium aluminum hydrotalcite sample 2.
[0065] Embodiment 6 This embodiment prepares a polyvinyl chloride sheath material, and the preparation steps are as follows: 1. According to the mass ratio of phosphoric acid: modified magnesium aluminum hydrotalcite: polyvinyl chloride: ethanol = 10:6:100:300, 98wt% of phosphoric acid, the modified magnesium aluminum hydrotalcite sample 1 obtained in Example 4, the carboxylated polyvinyl chloride sample 1 obtained in Example 2 and ethanol are mixed, and heated to 85°C for reflux reaction for 2h, during which cyclohexane is used as a water-carrying agent for timely dehydration, and phosphoric acid and ethanol are recovered after the reaction is completed, and the solids are extracted and washed with water once, and infrared dried at 100°C to obtain a first mixture; 2. According to the mass ratio of polyvinyl chloride: polyethylene: ethylene-vinyl acetate copolymer: titanium dioxide: diisodecyl phthalate: calcium zinc dimer acid: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]: glyceryl monostearate = 100:33:20:4:4:1.6:1:0.8:0.6, and according to the amount of polyvinyl chloride added in S1, weigh the other raw materials except polyvinyl chloride, mix them with the first mixture obtained in step 1, send them into a mixer, mix them at a speed of 600r / min at 80°C or above and 100°C for 20min, and extrude and granulate to obtain master batches with a diameter of 0.5mm to 1mm; wherein titanium dioxide is obtained through commercial procurement, and its particle size ranges from 50nm to 80nm; 3. The masterbatch is fed into a smelting device, melted in a temperature range of 180°C to 200°C for 20 minutes, and extruded by a single screw device to obtain a polyvinyl chloride sheath material sample 1.
[0066] It can be understood that if the extruded material is coated on the surface of the cable core in the above step 3, a photovoltaic cable can be obtained. In order to test the performance of the polyvinyl chloride sheath material in this embodiment, it is directly extruded and then cooled to form.
[0067] Embodiment 7 This embodiment prepares a polyvinyl chloride sheath material, and its preparation steps are the same as those of Example 6. The difference is that this embodiment uses the modified magnesium aluminum hydrotalcite sample 2 obtained in Example 5 and the carboxylated polyvinyl chloride sample 2 obtained in Example 3 to obtain the polyvinyl chloride sheath material sample 2.
[0068] Embodiment 8 This embodiment prepares a polyvinyl chloride sheath material, and its preparation steps are the same as those of Example 6. The difference is that this embodiment uses the modified magnesium aluminum hydrotalcite sample 2 obtained in Example 5 and the carboxylated polyvinyl chloride sample 1 obtained in Example 2 to obtain the polyvinyl chloride sheath material sample 3.
[0069] Embodiment 9 This embodiment prepares a polyvinyl chloride sheath material, and its preparation steps are the same as those of Example 6. The difference is that this embodiment uses the modified magnesium aluminum hydrotalcite sample 1 obtained in Example 4 and the carboxylated polyvinyl chloride sample 2 obtained in Example 3 to obtain the polyvinyl chloride sheath material sample 4.
[0070] Embodiment 10 This embodiment prepares a polyvinyl chloride sheath material, and its preparation steps and the selection of raw materials for the modified magnesium aluminum hydrotalcite sample 1 and the carboxylated polyvinyl chloride sample 1 are the same as those in Example 6, except that the titanium dioxide used in this embodiment is different from that in Example 6. The titanium dioxide selected in this embodiment is a titanium dioxide powder prepared from three powders of different particle sizes obtained by cyclone classification, and a polyvinyl chloride sheath material sample 5 is obtained.
[0071] The preparation method of titanium dioxide selected in this embodiment is as follows: taking 100g as an example, each 100g of titanium dioxide includes: 20g of titanium dioxide powder A, 50g of titanium dioxide powder B and 30g of titanium dioxide powder C. The particle size of titanium dioxide powder A ranges from 50nm to 80nm, the particle size of titanium dioxide powder B ranges from 120nm to 150nm, and the particle size of titanium dioxide powder C ranges from 200nm to 250nm.
[0072] Embodiment 11 In this embodiment, a polyvinyl chloride sheath material is prepared, and its preparation steps are the same as those in Example 6 to obtain polyvinyl chloride sheath material sample 6. The difference is that the polyvinyl chloride used in this embodiment is obtained through commercial procurement and has not been carboxylated. The magnesium aluminum hydrotalcite sample used in this embodiment is prepared by the following steps: 1. Dissolve ammonium sulfate in water at room temperature and stir evenly at a mass ratio of ammonium sulfate to water = 2:100 to obtain an aqueous phase; 2. Dissolve 2,2',4,4'-tetrahydroxybenzophenone in N-methylpyrrolidone at room temperature and stir evenly according to the mass ratio of 2,2',4,4'-tetrahydroxybenzophenone to N-methylpyrrolidone = 6:100 to obtain an organic phase; 3. The magnesium aluminum hydrotalcite prepared in Example 1, the aqueous phase, and the sodium dodecyl sulfate were ultrasonically dispersed for 20 min in a mass ratio of magnesium aluminum hydrotalcite: aqueous phase: organic phase: sodium dodecyl sulfate: cyclohexane = 15:50:30:3:40, and the organic phase and cyclohexane were added and mixed, and ultrasonically treated at a frequency of 60 kHz for 20 min using a 400 W ultrasonic device to obtain an emulsion, which was fed into a reactor and subjected to a hydrothermal treatment for 2.5 h at a temperature of 140° C. and a pressure of 3.5 MPa. After the hydrothermal treatment, the temperature was lowered and the pressure was released, and the solid was filtered, washed twice with acetone and water respectively, and dried to obtain magnesium aluminum hydrotalcite.
[0073] Performance Testing The present invention tests the performance of polyvinyl chloride sheath material samples 1 to 6, and the detection standards of tensile strength and elongation at break refer to GB / T1701-2001. In order to measure the anti-ultraviolet aging effect of the samples, the aging test conditions (temperature 80°C, time 144h) refer to the aging conditions of the non-electrical test of polyvinyl chloride sheath in GB / T5023, and 254nm short-wave ultraviolet irradiation with a power density of 100W / cm is applied during the aging process.
[0074] The results of the above performance tests are shown in Table 1. The test results show that although the mechanical properties of sample 5 obtained in Example 10 are the best before aging treatment, the mechanical properties of the five samples prepared in Examples 6 to 10 before aging treatment are relatively different. After aging treatment, the mechanical properties of sample 5 obtained in Example 10 and sample 1 obtained in Example 6 are both relatively good. After aging treatment, the mechanical properties of sample 6 obtained in Example 11 have declined the most, indicating that its anti-ultraviolet aging performance is poor.
[0075] It should be noted that the formula and test used in this embodiment are only used to verify the feasibility of the technical solution of this application. Based on the technical solution of this application, those skilled in the art can continue to add other fillers to improve the mechanical properties or other properties of the material according to actual needs.
[0076] Table 1 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a photovoltaic cable resistant to ultraviolet aging, characterized in that: include: S1, mixing and granulating raw materials including polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, modified magnesium aluminum hydrotalcite, titanium dioxide and additives to obtain masterbatch; S2, melt-extrude the masterbatch, and coat the masterbatch on the surface of the cable core as a sheath layer to obtain the photovoltaic cable; The modified magnesium aluminum hydrotalcite is subjected to intercalation treatment, and the intercalation agent used in the intercalation treatment includes ammonium salt and hydroxybenzophenone.
2. The preparation method according to claim 1, characterized in that: Taking the total addition amount of the titanium dioxide as 100wt%, the titanium dioxide comprises: Titanium dioxide powder A, 20wt% to 25wt%; Titanium dioxide powder B, 45wt% to 50wt%; Titanium dioxide powder C, 30wt% to 35wt%; Wherein, the average particle size D50 of the titanium dioxide powder A is A Smaller than the average particle size D50 of the titanium dioxide powder B B The average particle size D50 of the titanium dioxide powder B is B Smaller than the average particle size D50 of the titanium dioxide powder C C .
3. The preparation method according to claim 2, characterized in that: The particle size range of the titanium dioxide powder A is greater than 50 nm and less than 100 nm, the particle size range of the titanium dioxide powder B is greater than 100 nm and less than 200 nm, and the particle size range of the titanium dioxide powder C is greater than 200 nm and less than 350 nm.
4. The preparation method according to claim 1, characterized in that: In S1, by mass ratio, polyvinyl chloride: Polyethylene: ethylene-vinyl acetate copolymer: modified magnesium aluminum hydrotalcite: titanium dioxide: additive = 100: (30-35): (20-25): (6-12): (4-6): (2-6); and / or In S1, based on the total amount of the additives added as 100wt%, the additives include: 35wt% to 40wt% of a plasticizer, diisodecyl phthalate, 25wt% to 30wt% of a stabilizer, calcium zinc dimerate, 10wt% to 20wt% of an antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 15wt% to 25wt% of a lubricant, glyceryl monostearate; and / or In S1, the polyethylene is a linear low density polyethylene; and / or The cable core comprises, from inside to outside, a conductor, a conductor shielding layer, an insulating layer, and an insulating shielding layer.
5. The preparation method according to claim 1, characterized in that: In S1, the mixing temperature of the mixing and granulation is 80° C. to 100° C., the mixing speed is 400 r / min to 800 r / min, and the mixing time is 20 min to 30 min; and / or In S2, the melt extrusion has a melting temperature of 160°C to 220°C and a melting time of 20min to 40min.
6. The preparation method according to any one of claims 1 to 5, characterized in that The polyvinyl chloride is subjected to carboxyl modification treatment, the intercalant further comprises serine, and the polyvinyl chloride and the modified magnesium aluminum hydrotalcite are organically linked through an esterification reaction.
7. The preparation method according to claim 6, characterized in that: The carboxylation modification treatment comprises: using a compound having at least one carboxyl group and at least one thiol group to react with polyvinyl chloride particles by heating and refluxing in a solvent system; and / or The esterification reaction is carried out under heating conditions with an inorganic acid as catalyst.
8. The preparation method according to claim 6, characterized in that: S1 specifically includes: S11, mixing the polyvinyl chloride and the modified magnesium aluminum hydrotalcite, using an acid as a catalyst, heating and refluxing in a solvent system to obtain a first mixture; S12, mixing and granulating the first mixture with the polyethylene, the ethylene-vinyl acetate copolymer, the titanium dioxide and the auxiliary agent to obtain the masterbatch.
9. The preparation method according to claim 6, characterized in that: The modified magnesium aluminum hydrotalcite is prepared by the following steps: A1, dissolving the ammonium salt and the serine in water to obtain an aqueous phase; A2, dissolving the hydroxybenzophenone in N-methylpyrrolidone to obtain an organic phase; A3, firstly uniformly dispersing the magnesium aluminum hydrotalcite, the aqueous phase and sodium dodecyl sulfate by ultrasonication, then adding the organic phase and cyclohexane, mixing and ultrasonically emulsifying to obtain an emulsion; A4. The emulsion is fed into a reactor and subjected to hydrothermal treatment under heating and pressurization conditions to obtain the modified magnesium-aluminum hydrotalcite.
10. A photovoltaic cable resistant to ultraviolet aging, characterized in that: The UV-resistant photovoltaic cable is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Hydrotalcite like-polyamide functional nanocomposite and preparation method thereof
CN103554484A
Preparation method of amino acid ion intercalated MgFe-LDHs composite coating
CN119392334A
Nanocomposite compositions and processes for making the same
US20070105998A1
Nucleophilic substitution of chlorine containing polymers in aqueous medium by amido-thiolate groups
US4735997A
Process for preparing a polymer composition comprising hydrotalcites intercalated with active molecules, composition thus obtained and shaped articles comprising the same
WO2013060738A1